Estrogenic compound attenuates angiotensin II-induced vascular smooth muscle cell proliferation through interaction between LKB1 and estrogen receptor α - Sun Ae Kim; Kyung Young Lee; Jae-Ryong Kim; Hyoung Chul Choi (Journal of Pharmacological Sciences, 2016)
The prevalence rate of cardiovascular disease is higher for males than females, and estradiol (E2) induces AMP-activated protein kinase (AMPK) activation, which is known to regulate proliferation of VSMC. We identified the estrogenic properties of nordihydroguaiaretic acid (NDGA, a lignan phytoestrogen) that inhibit VSMC proliferation and explored the underlying mechanisms. Both the phosphorylation and expression of LKB1 were increased by NDGA. In addition, NDGA significantly attenuated angiotensin II (Ang II)-induced VSMC proliferation. To elucidate the estrogenic effects, we confirmed that NDGA increased estrogen receptor α (ERα) expression, similar to treatment with E2 and estriol (E3). Furthermore, tamoxifen and ERα siRNA obstructed the effects of NDGA including ERα expression, AMPK phosphorylation and both LKB1 phosphorylation and expression. VSMC proliferation was restored by tamoxifen and ERα siRNA. LKB1 siRNA also reversed the NDGA-mediated inhibition of VSMC proliferation. The estrogenic activity of NDGA induced LKB1 translocation from nucleus to cytosol, and tamoxifen obstructed LKB1 translocation. The absence of LKB1 completely abolished the increase of ERα expression induced by NDGA. Taken together, the beneficial effects of estrogenic compound (E2 and NDGA) on inhibition of VSMC proliferation are mediated by interaction between LKB1 and ERα, suggesting a potential mechanism for females having less cardiovascular disease.